Sustainable Material Substitutes for Stop motion Puppet Exteriors - Ruslan, Qistina; Mahmud, Nadia; Nasseri, Edina (International Journal of Membrane Science and Technology, 2023)
Sustainability with the materials used for the purposes of art are a par- adox which artists face; does the message brought forward by art outweigh the waste it produces? Central to this research is the production of stop motion puppet “fleshing” also known as the exterior of a stop motion puppet and the materials used to create it. It is the nature of stop motion animation to craft physical char- acters, props, and environments in order to animate. Vastly different from its counterpart, CGI (Computer Generated Imagery) animation, in which the entire animation is modelled digitally producing no physical waste; the single use na- ture of stop motion animation props deters enthusiasts from pursuing the craft. In addition to this issue, materials used in stop motion animation are usually purpose built in which it serves no purpose after being used in animation. As a result, productions produce large amounts of waste post animation. It is imperative to discuss the importance of exploration in materials conventionally used in non- animation disciplines and its potential application towards stop motion anima- tion. This research aims to find parallels in alternative material’s properties to enable the use of non-specialist products and its ability to be reused.